2018
DOI: 10.18535/ijsrm/v6i4.em08
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perception of Use, Ease, Security and Confidentiality to Use E-Filing (Study In The Tax Office Pratama Raba Bima)

Abstract: The research aim to examine and analyze the effect of perception of use, perception of ease, security and confidentiality to use of e-filing of the corporate taxpayer. The population in this study the number of taxpayers registered in the Tax Office Pratama Raba Bima which consists of Dompu Regency, Bima and Bima City amounted to 350 corporate taxpayers. The sampling technique is done by proportional stratified random sampling of 75 taxpayers. The research instrument is in the form of questionnaire and the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Likewise, if WPs feel that e-Filing is easy to use, then the level of intention to it is also increasing. A system can be said to be quality if it is designed to meet user satisfaction through the ease in using it; it is not only the ease to learn and use the system, but it also the ease of doing a job or task, where users will find it easier to work using the system than do it manually (Aryani et al, 2018;Le, Ngo, Trinh, & Nguyen, 2020;Nguyen, 2020;Nguyen & Luu, 2020;Phan, Nguyen, & Bui, 2019). The ease, in this case, is not only limited to the ease of using e-Filing, but also related to whether this system eases them in completing SPT filling compared to doing it traditionally.…”
Section: Perceived Ease Toward Intention To Use E-filingmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, if WPs feel that e-Filing is easy to use, then the level of intention to it is also increasing. A system can be said to be quality if it is designed to meet user satisfaction through the ease in using it; it is not only the ease to learn and use the system, but it also the ease of doing a job or task, where users will find it easier to work using the system than do it manually (Aryani et al, 2018;Le, Ngo, Trinh, & Nguyen, 2020;Nguyen, 2020;Nguyen & Luu, 2020;Phan, Nguyen, & Bui, 2019). The ease, in this case, is not only limited to the ease of using e-Filing, but also related to whether this system eases them in completing SPT filling compared to doing it traditionally.…”
Section: Perceived Ease Toward Intention To Use E-filingmentioning
confidence: 99%
“…The perception of utility directly affects intention to try and use the e-Filing system. If taxpayers feel the benefits, they will intend to use the system; otherwise, if they do not feel the benefits of the system, then they will not intend to use it (Aryani et al, 2018). Several studies (Rekayana, 2016;Zaidi et al, 2017) examined the effect of perceived usefulness on intention to use e-Filing.…”
Section: Perceived Usefulness Toward Intention To Use E-filingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the definitions from Hartono et al (2014) were used that perceived confidentiality is government employees' belief if his/her data will not be disclosed to an unauthorized party. A recent study by Aryani, Herwanti, and Basuki (2018) showed that perceived confidentiality had a positive and significant effect on interest in using e-filing. In the context of cloud computing, perceived confidentiality indicates the users' trust toward vendors (service providers) that can prevent incorrect information or data revealing.…”
Section: Perceived Confidentialitymentioning
confidence: 99%
“…The increase in social media usage reflects how consumers depends on UGC to search out travel information. Recent studies propose that tourists' personal experiences and exposure, amplified by social media's emotional contagion and information dissemination, can substantially impact their travel views, intentions, and future behaviour (Aryani et al, 2018;Manap & Adzharudin, 2013;Morand et al, 2021;Nguyen, 2020). Besides, it is essential to understand the changes on/from the demand side, as proposed by various researchers such as Nair and Sinha (2020), , Kour et al (2020) and Zenker and Kock (2020).…”
Section: Introductionmentioning
confidence: 99%